2019
DOI: 10.7717/peerj.7555
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free supernatants from cultures of lactic acid bacteria isolated from fermented grape as biocontrol againstSalmonellaTyphi andSalmonellaTyphimurium virulence via autoinducer-2 and biofilm interference

Abstract: Background Salmonella Typhi and Salmonella Typhimurium are the causative pathogens of salmonellosis, and they are mostly found in animal source foods (ASF). The inappropriate use of antibiotics enhances the possibility for the emergence of antibiotic resistance in pathogens and antibiotic residue in ASF. One promising alternative to antibiotics in animal farming is the use of lactic acid bacteria (LAB). Methods The present study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…Cell-free culture supernatants (CFCS) produced from LAB (LAB-CFCS) contain active substances and bacteriocins [ 24 ]. There have been demonstrated that LAB-CFCS can inhibit the growth of pathogenic bacteria E. coli O157:H7 [ 25 ], Gardnerella vaginalis [ 26 ], Listeria monocytogenes [ 27 ], Salmonella Typhi, Salmonella Typhimurium [ 28 ], Shigella flexneri [ 29 , 30 ] , Shigella sonnei [ 30 ], Staphylococcus aureus [ 31 ], and Streptococcus suis [ 32 ]. However, the studies of the efficacy of LAB-CFCS with its AMPs against pathogenic E. coli in pigs are scarce and under investigation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free culture supernatants (CFCS) produced from LAB (LAB-CFCS) contain active substances and bacteriocins [ 24 ]. There have been demonstrated that LAB-CFCS can inhibit the growth of pathogenic bacteria E. coli O157:H7 [ 25 ], Gardnerella vaginalis [ 26 ], Listeria monocytogenes [ 27 ], Salmonella Typhi, Salmonella Typhimurium [ 28 ], Shigella flexneri [ 29 , 30 ] , Shigella sonnei [ 30 ], Staphylococcus aureus [ 31 ], and Streptococcus suis [ 32 ]. However, the studies of the efficacy of LAB-CFCS with its AMPs against pathogenic E. coli in pigs are scarce and under investigation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among more than one hundred LAB strains isolated from fermented food samples, W. viridescens WM33 showed a strong inhibitory effect against Salmonella spp. [ 75 ]. The cell-free culture supernatants of the WM33 strain inhibit Salmonella serovars but the precise molecules involved in this effect were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the MIC value of LN66 CFS, we performed the method described by Pelyuntha with some modifications [ 15 ]. The cell concentrations and the culture system were the same as described above for the antibiotic MIC assay except that the two-fold dilutions of antibiotics were replaced with 5–50% ( v/v ) CFS diluted in BB containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%